Google Sites Improves Student Learning Outcomes on Plant Material: Google Sites Meningkatkan Hasil Belajar Siswa pada Materi Tumbuhan - Ihsan Basyori, Sansan (Indonesian Journal of Innovation Studies, 2025)
General Background: The integration of digital platforms in primary education has become increasingly vital to support engaging and accessible learning environments. Specific Background: In the context of Ilmu Pengetahuan Alam dan Sosial (IPAS) for Grade IV students, instructional delivery often lacks interactivity, reducing student engagement and learning outcomes. Knowledge Gap: While Web Learning has been widely explored, limited studies specifically assess the impact of Google Sites as a medium in IPAS instruction, particularly on the topic of plant body parts. Aims: This study investigates the effectiveness of Web Learning based on Google Sites in enhancing student learning outcomes in IPAS. Results: Employing a one-group pretest-posttest quasi-experimental design, findings revealed a significant improvement in posttest scores compared to pretest scores. Students also expressed highly positive responses toward the digital platform, indicating enhanced motivation and satisfaction. Novelty: This research contributes by highlighting Google Sites as a low-barrier, interactive web platform that can be seamlessly integrated into elementary science education. Implications: The results suggest that educators can effectively utilize Google Sites to enrich learning experiences and improve educational outcomes in IPAS, fostering greater student engagement with scientific content. Highlights:  Enhances student engagement through interactive content. Significantly improves posttest learning outcomes. Offers practical, accessible tools for classroom use. Keywords: Web Learning, Google Sites, Student Learning Outcomes, Primary Education, IPAS Instruction